2010
DOI: 10.1186/1743-422x-7-378
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic analysis of classical swine fever virus E2 glycoprotein using pig antibodies identifies residues contributing to antigenic variation of the vaccine C-strain and group 2 strains circulating in China

Abstract: BackgroundGlycoprotein E2, the immunodominant protein of classical swine fever virus (CSFV), can induce neutralizing antibodies and confer protective immunity in pigs. Our previous phylogenetic analysis showed that subgroup 2.1 viruses branched away from subgroup 1.1, the vaccine C-strain lineage, and became dominant in China. The E2 glycoproteins of CSFV C-strain and recent subgroup 2.1 field isolates are genetically different. However, it has not been clearly demonstrated how this diversity affects antigenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 41 publications
4
45
0
1
Order By: Relevance
“…The virus neutralization test (VNT) to determine neutralizing antibody titre in serum samples was carried out as previously described (Chen et al, 2010). Briefly, 50 lL of 100 TCID 50 CSFV Brescia strain were mixed with an equal volume of twofold serially diluted pig sera in a 96-well plate and incubated at 37°C for 1 h before 100 lL of DMEM containing 1 9 10 5 /mL SK6 cell, 10% FBS and 1X antibiotic-antimycotic was added to all wells in 96-well plates.…”
Section: Serum Anti-csfv Neutralization Antibody Assay (Immunization mentioning
confidence: 99%
“…The virus neutralization test (VNT) to determine neutralizing antibody titre in serum samples was carried out as previously described (Chen et al, 2010). Briefly, 50 lL of 100 TCID 50 CSFV Brescia strain were mixed with an equal volume of twofold serially diluted pig sera in a 96-well plate and incubated at 37°C for 1 h before 100 lL of DMEM containing 1 9 10 5 /mL SK6 cell, 10% FBS and 1X antibiotic-antimycotic was added to all wells in 96-well plates.…”
Section: Serum Anti-csfv Neutralization Antibody Assay (Immunization mentioning
confidence: 99%
“…and reports of disease outbreaks by CSFV genotype 1 have been limited to Central and South America (Postel et al., ; Silva et al., ). One suggested reason for a global switch in predominant viral genotype is that all CSFV vaccine strains target genotype 1 (Chen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The CSFV-2.1E2 vaccine did not produce complete protection, as indicated by the fever exhibited by two rabbits from this group and the presence of viral RNA in the spleen. Previous phylogenetic analysis showed that subgroup 2.1 viruses branched away from subgroup 1.1, the vaccine C-strain lineage [22]. The C-strain is an attenuated virus through repeated passages of virulent strain Shimen in rabbits.…”
Section: Groupsmentioning
confidence: 99%
“…Commercially available vaccines based on C-strain are effective and provide complete protection against the three groups of CSFV but could not offer differentiability of infected from vaccinated animals [20,21]. The CSFV vaccine C-strain and subgroup 2.1 strains of the glycoprotein E2 have antigenic variations that are primarily determined by an amino acid sequence (702-731 aa) [22]. The commercial CSFV E2 subunit vaccines BAYOVAC ® CSF Marker and Porcilis ® Pesti are derived from genotype 1; these vaccines do not completely protect against the heterologous strain of genotype 2.1, which may be related to antigenic variations among different genotypes [3,21].…”
Section: Introductionmentioning
confidence: 99%